Aktivitas Sitotoksik dan Antiproliferasi Fraksi n-Heksan Biji Al-pukat (Percea americana Mill.) Terhadap sel T47D - Juwita Rahmawati; Maryati Maryati (Universitas Muhammadiyah Surakarta, 2021)
Avocado plants are widely used as traditional medicine in Indonesia. This research aimed to determine the cytotoxic and antiproliferation activity of avocado seed extract and fractions on the T47D breast cancer cell line. Extraction was done by maceration method using 96% ethanol, then fractionation was done by liquid-liquid partition using n-hexane, chloroform, and ethyl acetate. Cytotoxic and antiproliferation tests were done by the MTT method. Apoptosis activity was investigated by the double staining method, using acridine orange-propidium iodide as a staining reagent. Results showed that the n-hexane fraction of avocado seed had a cytotoxic activity with IC50 27.9 µg/mL. N-hexane fraction of avocado seed inhibited proliferation and induced apoptosis of T47D cell line.